STRATEGI KOMUNIKASI PEMASARAN KAMPOENG BATIK KAUMAN PEKALONGAN - Kun Cahyaningrum (JURNAL LITBANG PROVINSI JAWA TENGAH, 2014)
The purpose of this study describes marketing communication strategy which perfomed by Kampoeng Batik Kauman and Government, then analyze about synergy communication between Kampoeng Batik Kauman and Government. This study used a descriptive case study method. This study used primary data are in-depth interviews, while the secondary data used document and online data. The technique used the validity of data triangulation source. This study used data analysis techniques, which were data reduction, the data display and conclusion drawing / verification. The results of this study indicate that Kampoeng Batik Kauman use advertising, sales promotion, special event, public relation, direct marketing, and personal selling to promote batik industry. The success of these activities effect on the level of consumers awareness about adventages, benefits, and product attributes of SME (Small and Medium Enterprises) Kampoeng Batik Kauman. Meanwhile Government use advertising, special event, and public relation to promote batik industry. The success of these activities effect on the level income of businessman and tourism development.